The Influence Of Cultural And Religious Dimensions On Tax Fraud - Darwis Lannai; Muslim Muslim; Andi Naurah Afifah; Hamzah Ahmad (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2020)
Culture and religion shape people's attitudes in their daily activities. However, there are also many violations of attitudes committed by some groups of society, including tax fraud. Based on this phenomenon, this study aims to analyze and obtain empirical evidence about the influence of cultural dimensions (power distance, individualism, uncertainty avoidance, masculinity) and religiosity on the level of tax fraud. The population of this study is an individual taxpayer registered at KPP Pratama Makassar Utara. The sampling technique used was identical sampling. Of the 100 questionnaires distributed, 100 respondents participated. The regression analysis results show that power distance, uncertainty avoidance, and masculinity positively affect tax fraud, but high religiosity hurts tax fraud. The results showed that individualism had no impact on the level of tax fraud.